2013
DOI: 10.1149/2.015306jes
|View full text |Cite
|
Sign up to set email alerts
|

Triblock Copolymers as Suppressors for Microvia Filling via Copper Electroplating

Abstract: In this work, ethylene-propylene-ethylene (EPE) oxide triblock copolymers were found to be effective suppressors for microvia filling during copper electroplating. The studied EPE copolymers were divided into two groups according to their solubility and compositions. The first group was composed of EPE 1000, EPE 2000, and EPE 3500, and the second group contained EPE 2450, EPE 2900, and EPE 8000. In particular, the function of the triblock copolymer suppressors (e.g. EPE 2900) and their synergistic effect with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The aspect ratio of recessed features that can be filled by superconformal copper deposition is dependent on the dynamic range available between suppressed and actively growing surfaces. The search for more effective suppressors has largely focused on more complex polyethers ranging from block copolymers to star-shaped block copolymers as well as exploration of the role of fixed charges. ,, Herein, two different classes of polyethers, poloxamer and poloxamine, have been selected to examine the role of oligomer chemistry and secondary structure in the adsorption process (see Figure ). Poly­(propylene oxide) (PPO) is the largest component in both molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The aspect ratio of recessed features that can be filled by superconformal copper deposition is dependent on the dynamic range available between suppressed and actively growing surfaces. The search for more effective suppressors has largely focused on more complex polyethers ranging from block copolymers to star-shaped block copolymers as well as exploration of the role of fixed charges. ,, Herein, two different classes of polyethers, poloxamer and poloxamine, have been selected to examine the role of oligomer chemistry and secondary structure in the adsorption process (see Figure ). Poly­(propylene oxide) (PPO) is the largest component in both molecules.…”
Section: Resultsmentioning
confidence: 99%
“…6 To meet industrial requirements, several additives, such as an accelerator, a suppressor, and a leveler, must be simultaneously added to the electroplating copper solution. 7 In this additive system, the accelerator not only combined with chloride ion enhanced copper deposition at the bottom but also improved grain structure of the electroplating copper; the suppressors quickly adsorbed on the copper surface in the presence of chloride ion, forming a saturated lm that seriously hindered diffusion of Cu 2+ to the copper surface and inhibited the copper deposition rate. 8,9 For the sake of improving microvia electroplating copper lling performance and promoting copper surface uniformity, the leveler also was added to the electroplating solution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the research on the traditional commercial suppressor PEG, some researchers have recently reported on the inhibitory behavior of some new suppressors on copper deposition. For example, Xiao et al [23] recently proposed a kind of triblock copolymer composed of ethylene-propylene-ethylene, which can also have a strong inhibitory effect on copper deposition. But its inhibitory effect is similar to that of PEG, depending on the concentration of chloride ions in the solution.…”
Section: Introductionmentioning
confidence: 99%